2022
DOI: 10.1371/journal.pone.0262103
|View full text |Cite
|
Sign up to set email alerts
|

The association of social capital with depression and quality of life in school-aged children

Abstract: Social capital is an important factor that affects mental health. The purpose of this study was to examine the relationship between social capital and depression and between social capital and quality of life (QoL) in children in elementary and junior high school and to examine how this relationship differs in relevant patterns at both the individual- and school-level. The study was conducted in all elementary and junior high schools in a single municipality; the subjects consisted of 3,722 elementary school a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Previous studies on Japanese adolescents before the COVID‐19 pandemic suggested that poor academic performance, disrupted daily routines, and fewer social interactions were associated with increased depressive and anxiety symptoms. 31 , 32 , 33 Future studies are needed to examine whether these relationships were strengthened by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on Japanese adolescents before the COVID‐19 pandemic suggested that poor academic performance, disrupted daily routines, and fewer social interactions were associated with increased depressive and anxiety symptoms. 31 , 32 , 33 Future studies are needed to examine whether these relationships were strengthened by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…School climate refers to the overall quality and character of the school experience, including the emotional and academic support provided by teachers and students, as well as opportunities for autonomy within the classroom [37,38]. A positive school climate can contribute to socialization, which is known to act as a protective factor for adolescents' mental health [14,39] Speci cally, strong connections between individuals, peers, and teachers can provide adolescents with valuable social support, enabling them to better cope with stressors and reduce the occurrence of abnormal psychological behaviors [40][41][42][43].…”
Section: Role Of Psychological Resilience In the Relationship Between...mentioning
confidence: 99%
“…Fourteen studies (Dassopoulos et al, 2012;Hamano et al, 2010;Huang et al, 2021;Huang et al, 2023;Jiang et al, 2020;Jonsson et al, 2020;Lagaert et al, 2021;Maass et al, 2016;Mao et al, 2022;Mohnen et al, 2011Mohnen et al, , 2014Mori et al, 2022;Morozumi et al, 2020;Nieuwenhuis, 2020, 87-92) have been found that address the relationship between NSC and mental health. Some studies look at the concept of mental health in general, others at self-rated health (selfrated health [SRH], life satisfaction [LS], quality of life [QoL]) and there is one specific study for the cognitive function defined in terms of memory, recall and retrieval (Jiang et al, 2020) and two for depression (Huang et al, 2023;Mao et al, 2022).…”
Section: Relationship Between Csa and The Psychological Health Of The...mentioning
confidence: 99%